A methodological framework to generate transit-oriented development (TOD) typologies - Robillard, Arianne; van Lierop, Dea; Boisjoly, Geneviève (Cities, 2025)
To support the implementation of transit-oriented development (TOD) in different contexts, researchers and planners increasingly use TOD typologies. While the methodologies developed to generate TOD typologies are frequently meant to be transferable across different contexts, no studies explicitly analyze and describe how to adapt these methodologies to other regions. Therefore, this paper examines which factors need to be considered when applying a TOD typology methodology to any given region. This paper provides a detailed description of the process of adapting an existing bicycle-oriented TOD typology methodology that was developed for Montreal (Canada) to another context in Rotterdam (the Netherlands). The transfer results in two distinct typologies by clustering stations based on their respective contexts. Based on the findings, we designed a five-step methodological framework to guide TOD typology development across diverse contexts. The five steps are: (i) identify the study area (public transport stations) and define the research or planning objectives underlying the development of the typology, (ii) identify indicators and the catchment area, (iii) select the classification methods, (iv) present the clustering results, and (v) discuss planning implications. This study is not a comparative analysis of classification results between Montreal and Rotterdam, but rather a critical analysis of the transferability of a TOD typology methodology, which has implications for any planning tool that is used beyond a single context. The proposed framework makes developing a TOD typology more accessible to planners and, therefore, supports the use of TOD typology in practice. •Transfer of a TOD typology tool from Montreal, Canada to Rotterdam, Netherlands.•Five-step methodological framework to design context-specific TOD typologies.•Contextualization of the tool based on the study area and planning objectives is key.•Proposed framework enables local station development policy recommendations.